Hybrid Uninterruptible Power Supply System for Irrigation of Vegetable Crops - Despotović, Željko V; Stevanović, Ilija R.; Rodić, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2023)
The paper presents the realization of a hybrid and uninterruptible power supply system based on green or renewable energy sources (solar and wind) which is used for irrigation of vegetable crops on the "smart land" at the location of the town Belegiš, which is located in the immediate vicinity of Belgrade and on the side of the Danube River. Within the power system are realized the photovoltaic power plant with an output AC power of 8 kW, the wind generator with a power of 0.5 kW and battery bank 48Vdc/720Ah. This three of power supplies are as primary power sources, while a diesel electric generator (DEG) with a power of 7.5 kW, is one auxiliary power source. In addition to this hybrid and uninterruptible power supply, a system for smart management for irrigation has been implemented. At the end of the paper will be present the experimental results obtained during the exploitation.